Dietary inflammatory index mediation lifestyle patterns and depression among women with osteopenia or osteoporosis - Wang, Baoping; Fan, Yuxin; Tang, Shaofang; Guo, Weihong; Li, Yin; Dai, Chenlin (Frontiers in Nutrition, 2025)
ObjectiveLifestyle factors play a critical role in osteoporosis management and are closely linked to the development and progression of comorbid depression. This study examines lifestyle patterns and their association with depression in individuals with osteopenia or osteoporosis, while assessing the mediating role of the Dietary Inflammatory Index (DII).MethodsData from the National Health and Nutrition Examination Survey (NHANES) 2009–2020 were analyzed using latent class analysis (LCA) to classify 3,384 adults based on their lifestyle behaviors. A generalized linear model (GLM) evaluated the effects of lifestyle patterns on depression, and mediation analysis tested associations between these patterns, DII, and Patient Health Questionnaire-9 (PHQ-9) scores.ResultsLCA identified three lifestyle groups: healthy but inactive (34.16%), unhealthy (8.78%), and sedentary (57.06%). The unhealthy (OR = 2.848, 95% CI = 1.550–5.234, p = 0.001) and sedentary (OR = 1.600, 95% CI = 1.127–2.271, p = 0.009) groups were associated with higher depression risk in women. DII partially mediated the relationships between unhealthy lifestyle and PHQ-9 (effect coefficient = 0.095, 95% CI: 0.056–0.135) and between sedentary lifestyle and PHQ-9 (effect coefficient = 0.059, 95% CI: 0.017–0.115).ConclusionThese findings suggest that lifestyle patterns significantly influence depression in women with osteopenia or osteoporosis, with DII serving as a partial mediator.